Maqāṣid al-Syarī‘ah dan Legislasi Nasional: Rekonstruksi Model Sistemik Berbasis Teori Sistem Jasser Auda - Muhibbussabry; Mhd. Syahnan; Hasan Matsum; Nispul Khoir (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This article examines Maqāṣid al-Syarī‘ah as a paradigm of modern legislation in the formation of Indonesian national law. The main issue addressed is the absence of a systematic methodological framework for integrating public interest values into the legislative process, causing lawmaking to often remain limited to formal validity without fully reflecting substantive justice. Previous studies have generally positioned maqāṣid as an interpretive framework or normative principle in Islamic legal reform, while its operationalization as a legislative methodology within national lawmaking remains limited. This study employs normative legal research with statutory, conceptual, and maqāṣidī approaches, using Jasser Auda’s systems theory as the analytical framework. The findings show that maqāṣid values have been substantially internalized in several areas of national law, particularly in marriage regulation, human rights protection, domestic violence prevention, environmental protection, and the safeguarding of human dignity. However, such integration remains partial, implicit, and has not yet been institutionalized as an operational instrument in lawmaking. The novelty of this article lies in reconstructing maqāṣid not merely as an ethical-normative principle, but as a systemic legislative methodology. This article proposes a maqāṣid-based legislative model consisting of five stages: identifying the objectives of Sharia, analyzing the social context, formulating legal norms, testing public interest, and conducting systemic evaluation. This model is expected to strengthen the development of national law oriented toward substantive justice, public welfare, human dignity, and social sustainability.